PENGARUH PROMOSI TERHADAP MINAT BELI ASURANSI X - Nasywa Chintami Rahmadani Putri; Yulisbet Hutapea (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
This study aims to analyze the influence of promotion on the purchase intention of health insurance. Promotion is a crucial marketing tool to attract the attention of potential consumers and increase the purchase intention of insurance products. The research method used is qualitative. The obtained data were analyzed using multiple linear regression to examine the effect of the independent variable (promotion) on the dependent variable (purchase intention). The effectiveness of promotional strategies enhances consumer interest in purchasing health insurance products. The results show that promotion has a significant impact on the purchase intention of health insurance. Promotional factors such as sales promotion and public relations positively contribute to increasing the purchase intention of health insurance.